Neonatal admission and mortality in babies born in UK alongside midwifery units: a national population-based case-control study using the UK Midwifery Study System (UKMidSS). Issue 2 (30th October 2020) - Rowe, Rachel; Soe, Aung; Knight, Marian; Kurinczuk, Jennifer J
Abstract : Objectives: To determine the incidence of and risk factors for neonatal unit admission, intrapartum stillbirth or neonatal death without admission, and describe outcomes, in babies born in an alongside midwifery unit (AMU). Design: National population-based case-control study. Method: We used the UK Midwifery Study System to identify and collect data about 1041 women who gave birth in AMUs, March 2017 to February 2018, whose babies were admitted to a neonatal unit or died (cases) and 1984 controls from the same AMUs. We used multivariable logistic regression, generating adjusted OR (aOR) with 95% CIs, to investigate maternal and intrapartum factors associated with neonatal admission or mortality. Results: The incidence of neonatal admission or mortality following birth in an AMU was 1.2%, comprising neonatal admission (1.2%) and mortality (0.01%). White 'other' ethnicity (aOR=1.28; 95% CI=1.01 to 1.63); nulliparity (aOR=2.09; 95% CI=1.78 to 2.45); ≥2 previous pregnancies ≥24 weeks' gestation (aOR=1.38; 95% CI=1.10 to 1.74); male sex (aOR=1.46; 95% CI=1.23 to 1.75); maternal pregnancy problem (aOR=1.40; 95% CI=1.03 to 1.90); prolonged (aOR=1.42; 95% CI=1.01 to 2.01) or unrecorded (aOR=1.38; 95% CI=1.05 to 1.81) second stage duration; opiate use (aOR=1.31; 95% CI=1.02 to 1.68); shoulder dystocia (aOR=5.06; 95% CI=3.00 to 8.52); birth weight <2500 g (aOR=4.12; 95% CI=1.97 to 8.60), 4000–4999 g (aOR=1.64; 95% CI=1.25 to 2.14) and ≥4500 g (aOR=2.10; 95% CI=1.17 to 3.76), were independently associated with neonatal admission or mortality. Among babies admitted (n=1038), 18% received intensive care. Nine babies died, six following neonatal admission. Sepsis (52%) and respiratory distress (42%) were the most common discharge diagnoses. Conclusions: The results of this study are in line with other evidence on risk factors for neonatal admission, and reassuring in terms of the quality and safety of care in AMUs. Abstract : Interesting national study of adverse events of babies born on UK midwifery units showing mortality and admission rate not raised (compared with obstetric units) and complications were uncommon.